GENRE SENI MUSIK GENERASI MUDA DI KOTA PEKANBARU - Saputra, Dheo; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in the Districts of Tampan and Marpoyan Damai, Pekanbaru City. This research aims to find out what music genres developed in Pekanbaru City in the last decade. Then, among all these genres, which music genre is the most prominent and influences young people in their social processes and behavior. This research was conducted on 8 informants in the 2 districts which have been determined by researchers and determined based on Purposive Sampling. The research instrument used interview, observation, and documentation guidelines. This study uses qualitative analysis techniques. Research conducted found that the genre of music that is popular today is pop, rock, blues, reggae, k-pop, indie, edm, and koplo. The young generation, as the main focus in this study, carried out several social processes in the form of imitations related to the genre of music they liked, such as the style of dress, stage action, and also the musician's instrument. Then, at the suggestion stage, they become fond of listening to their favorite genre of music continuously. At the identification stage, there are behaviors such as creating a community or association, the emergence of a music group, setting up a coffee shop based on a love of coffee and twilight, often uploading quotes on social media, and making music cover videos and uploading them to their social media. At the sympathy stage, they do things such as changing lifestyles (familiar with coffee and dusk), fond of reading books, studying popular genres, and fond of socializing.Keywords: Popular genre, Young generation.